A theoretical analysis on electronic structure of the (110) surface of TiO2-SnO2 mixed oxide - Sambrano, JR; Vasconcellos, L. A.; Martins, JBL; Santos, MRC; Longo, Elson [UNESP]; Beltran, A. (Elsevier B.V., 2003)
Mixed oxide compounds, such as TiO2-SnO2 system are widely used as gas sensors and should also provide varistor properties modifying the TiO2 surface. Therefore, a theoretical investigation has been carried out characterizing the effect of SnO2 on TiO2 addition on the electronic structure by means of ab initio SCF-LCAO calculations using all electrons. In order to take into account the finite size of the cluster, we have used the point charge model for the (TiO2)(15) cluster to study the effect on electronic structure of doping the TiO2 (110) Surface. The contracted basis set for titanium (4322/42/3), oxygen (33/3) and tin (43333/4333/43) atoms were used. The charge distributions, dipole moments, and density of states of doping TiO2 and vacancy formation are reported and analysed. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: mixed oxide; titanium oxide; surface defects; clusters; ab initio